Pengaruh Pengungkapan Modal Intelektual, Asimetri Informasi, dan Profitabilitas Terhadap Manajemen Laba Riil - Rantung, Diestri Margaret; Salim, Susanto (Politeknik Ganesha Medan, 2024)
The purpose of this study was to examine the effect of intellectual capital disclosure using Intellectus Model, information asymmetry, and profitability through the ratio of ROA (Return on Assets) on real earnings management in primary consumer goods companies that listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. This research is a quantitative study which using secondary data that were obtained from the official website of the Indonesia Stock Exchange (IDX) in the form of annual financial report. The sample selection used is purposive sampling method in order to obtain 25 companies. The criteria used in this study were as follows: sample selection criteria and for companies that have been registered since 2014, not classified as primary consumer goods or agricultural food product industry, and have complete financial report data from 2015-2019. The analysis technique used is Multiple Linear Regression (MLR) through the Statistical Package for the Science 25 (SPSS 25) program with data tabulated using Microsoft Excel. The results of this study indicate that: intellectual capital disclosure using Intellectus Model has no effect on real earnings management, information asymmetry has a positive effect on real earnings management, while profitability through the ratio of ROA have no effect on real earnings management.